Analysis of Raw Material Inventory Control for Smoothness of The Production Process Using MRP (Material Requirement Planning) Method at The Tofu Factory of Guyub Rukun in Malang City - Danda; Anung Prasetyo Nugroho; Yuni Setyawati (IRDH International Journal of Social Sciences & Humanities, 2025)
This research was conducted with the aim of finding out whether the analysis of raw material inventory control carried out by the Guyub Rukun tofu Factory was effective in the production process in Lowokwaru District Malang City, to find out how the raw material inventory control process works for the production process, The research design in this study is to use a quantitative approach method. This research using quantitative methods is research that aims to describe and understand the phenomena experienced by research subjects, for example regarding the analysis of raw material inventory control for the smooth running of the production process using the MRP method. In this study, the collected data was then processed using quantitative descriptive analysis. In general, quantitative data analysis involves three steps: observation, interviews, and documentation. This research was conducted at the Guyub Rukun Tofu Factory in Lowokwaru District, Malang City in June 2025. The results of this study are the raw material inventory control system implemented by the Guyub Rukun Tofu Factory in Malang City, the Guyub Rukun Tofu Factory implements a routine inventory control system and is based on daily operational experience, where every day the main raw material is purchased, namely soybeans, as much as 200 kg according to the daily production capacity. The application of the material requirement planning (MRP) method in planning raw material requirements at the Guyub Rukun tofu factory based on EOQ calculations, with an ordering cost of IDR 40,000 per order and a storage cost of IDR 717,000 per kg per year, obtained an optimal order size of around 818 kg per order. Thus, the effectiveness of the material requirements planning (MPR) method compared to the inventory control policies currently implemented by the Guyub Rukun Tofu factory.